Perancangan Website Penjualan Produk Usaha Gudang Sirine Menggunakan Metode Prototypyng - Surya Adji Pangestu; Yoga Pratama; Thoyyibah Tanjung (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Data collection when selling a product is very important for business actors. The manual method will still be used when collecting sales data. Therefore, you need a website that can collect data about the sales of your business products. This allows you to do this quickly, efficiently and accurately. Making a sales website is done through data collection, system analysis, system design, and system implementation. This system was built using the MySQL and PHP programming languages ​​for database management using the Codeigniter framework. As a result of this paper, a web-based application for a PHP-based store product sales information system has been created that allows shoppers to connect directly with sellers through their website anytime, anywhere. This application is expected to make the process of data collection and product sales easier and more efficient.